Gender Differences in Graduate Degree Choices - Judith M. Delaney; Paul J. Devereux (Institute of Labor Economics (IZA), 2024)
While gender differences in the decision of what to study at undergraduate level are much studied, there is relatively little attention paid to subsequent study decisions of graduates. Given the increased importance of graduate education in recent decades, these decisions can have major labour market implications. In this paper, we use administrative data from Ireland to study these choices. We find systematic and substantial differences by gender in choice of graduate field, even when taking account of the exact undergraduate programme attended and a large set of controls measuring academic interests and aptitudes. Female graduates are less likely to do further study in STEM fields and more likely to enter teaching and health programmes. When we explore the effect of these choices on early career gender gaps in earnings, we find that they tend to exacerbate earnings gaps. Even after accounting for the exact undergraduate programme and detailed school subject choices and grades, there is an 8% gender gap in earnings at age 33 for persons who pursued a graduate degree; the choice of graduate programme can explain about 15% of that gap.
Keywords: J16; J24; I21; I23; I24; I26; 330; gender gaps; graduate study; field of study; gender earnings gap; higher education